(untitled) (REMUNOM, 2026)
Mead is a fermented alcoholic beverage made from honey, still relatively unexplored in Brazil, especially when associated with the valorization of regional ingredients. The use of spices such as nutmeg can represent an alternative for product diversification and value addition. Thus, this study aimed to develop and characterize, from a physicochemical point of view, a mead produced with honey from Apis mellifera from northeastern Pará, flavored with nutmeg (Myristica fragrans) at different fermentation times (10, 20, and 30 days). Initially, the honey and nutmeg were characterized in terms of physicochemical parameters, ensuring the quality of the raw materials. Subsequently, a base mead was produced, followed by the addition of nutmeg and further fermentation. The physicochemical analyses performed on the meads included pH, electrical conductivity (EC), density, viscosity, alcohol content, total soluble solids (TSS), titratable acidity, and dry residue, with statistical treatment of the data. The results indicated that the addition of nutmeg increased the pH and EC values and reduced the viscosity, while the alcohol content and TSS did not undergo significant changes. Titratable acidity was the variable most influenced by the flavoring time, showing a decreasing linear behavior. Thus, nutmeg exerts a relevant influence on the physicochemical characteristics of mead, highlighting acidity as a possible indicator of the beverage's preparation time.